2022
DOI: 10.3390/analytica3010009
|View full text |Cite
|
Sign up to set email alerts
|

Oil Media on Paper: Investigating the Effect of Linseed Oils on Pure Cellulosic Paper Supports. A Research Matter of Damage Assessment

Abstract: Oil media on paper, such as oil paintings, sketches, prints, and books, occasionally present problems associated with the effect of oil medium on the paper support, raising a composite matter of condition assessment as it depends on several factors. The present work examines the effect of linseed oil on paper and, in particular, the changes caused by three types of linseed oil on the optical, morphological, mechanical, and chemical properties of pure cellulosic paper, employing mock-ups submitted to artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…A small number of research works on this matter have published in the past, though they do not provide adequate results to compensate to the interpretation of alterations and problems recorded in original works [7][8][9][10]. Recently, the authors of the present work reported the initial results of an investigation into the effect of linseed oils on pure cellulosic paper [11]. Specifically, we have researched the changes in the optical, morphological, mechanical, and chemical properties of pure cellulosic paper mock-ups impregnated with three types of linseed oil, subjected to thermal-humid ageing in air-tight vessels.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…A small number of research works on this matter have published in the past, though they do not provide adequate results to compensate to the interpretation of alterations and problems recorded in original works [7][8][9][10]. Recently, the authors of the present work reported the initial results of an investigation into the effect of linseed oils on pure cellulosic paper [11]. Specifically, we have researched the changes in the optical, morphological, mechanical, and chemical properties of pure cellulosic paper mock-ups impregnated with three types of linseed oil, subjected to thermal-humid ageing in air-tight vessels.…”
Section: Introductionmentioning
confidence: 75%
“…The research followed the exact methodology applied to the investigation on pure cellulosic paper supports reported in previous work carried out by the authors of this work [11]. Experimental work included colorimetry, opacity, tensile strength, pH measurements, SEM, FTIR, and VOC analysis with GC-MS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations